Avaliação e redesenho do sistema gerencial de assistência estudantil da UFPA baseados na engenharia semiótica - RODRIGUES, Renan Eduardo Soares (2025)
The interface of software has high importance for the interaction as well as the user ́s acceptance. A system with communicability problems can cause waiver of its use if the user does not have the necessary support from the developer. As the developer may not be present next to the user in most cases, it is necessary that the system represents it completely, because the system is the voice of the developer or system designer at time of interaction with the user. O Sistema Gerencial de Assistência Estudantil (SIGAEst) is an example where there are many users who, with very little knowledge of technology, have the need to use the system. Many of these users have difficulties in following all necessary steps to get sign up to run for one of the aid offered by the University, causing a constant contact to request for help. This paper presents a review and redesign of communicability of SIGAEst to solve problems between the system and users. We primarily use techniques based on Semiotic Engineering to evaluate, inspect and redesign the interfaces of the system searching for the best user interaction. The results obtained in this project were satisfactory, in view of the fact that the assessment that was carried out with users, after the redesign of the system, did not show any user with difficulties in time to carry out the steps that have been requested.